Cardiovascular Risk Factor Burden in Veterans and Non-Veterans with Parkinson Disease - Kotagal, Vikas; Albin, Roger L.; Müller, Martijn L.T.M; Bohnen, Nicolaas I. (Journal of Parkinson's disease, 2018)
Background: Medical comorbidities, including cardiovascular risk factors such as hypertension and diabetes, influence disease progression in Parkinson disease (PD) and may be variably present in different clinical populations. Objective/Methods: We conducted a retrospective nested case-control study of 29 Veterans with PD and 29 non-Veteran PD controls. The groups were matched for age, gender, and disease duration. Both groups underwent clinical and imaging testing as part of their participation in a larger cross-sectional PD observational study at our research center. Veterans were recruited primarily from movement disorders neurology clinics at the Ann Arbor Veterans Affairs (VA) Health System. Non-Veterans were recruited primarily from analogous clinics at the University of Michigan Health System. We explored differences in cardiovascular risks factor burden between the groups. Results: Veterans with PD showed higher scores on the simplified Framingham 10-year general cardiovascular disease risk calculator (FR score; 27.3% (11.5) vs. 20.7% (6.8); t = –2.66, p = 0.011) and fewer years of self-reported education (14.5 (2.5) vs. 16.7 (2.6); t = 3.33, p = 0.002). After adjusting for age, disease duration, education, and the use of antihypertensive medications, Veterans showed higher FR scores (t = 2.95, p = 0.005) and a higher intra-subject ratio of FR score to age-and-gender normalized FR score (t = 2.49, p = 0.016), representing an elevated component of modifiable cardiovascular risk factor burden. Conclusion: Cardiovascular comorbidities are common in Veterans with PD and may be more severe than in non-Veteran PD populations. These findings merit replication in other representative cohorts. Veterans may be a preferred population for clinical trials evaluating cardiovascular risk factor management on PD progression.